2016
DOI: 10.1080/0740817x.2015.1126004
|View full text |Cite
|
Sign up to set email alerts
|

Optimization models to integrate production and transportation planning for biomass co-firing in coal-fired power plants

Abstract: Co-firing biomass is a strategy that leads to reduced greenhouse gas emissions in coal-fired power plants.Incentives such as production tax credit (PTC) are designed to help power plants overcome the financial challenges faced during the implementation phase. Decision makers at power plants face two big challenges.The first challenge is identifying whether the benefits from incentives such as PTC can overcome the costs associated with co-firing. The second challenge is identifying the extent to which a plant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Gubba et al [15] suggested level of straw co-firing of 12% on thermal basis using particle heat-up model. However, only a limited number of studies have dealt with the logistics costs to estimate co-firing ratio [17,18]. Berggren et al [17] developed a cost optimizing linear programming model to investigate the potential for co-firing of biomass and coal in the Polish power-generation system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Gubba et al [15] suggested level of straw co-firing of 12% on thermal basis using particle heat-up model. However, only a limited number of studies have dealt with the logistics costs to estimate co-firing ratio [17,18]. Berggren et al [17] developed a cost optimizing linear programming model to investigate the potential for co-firing of biomass and coal in the Polish power-generation system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Key parameters used in their model included boiler retrofit cost, operation/maintenance cost, and fuel cost, including transportation cost. Eksioglu et al [18] proposed a model that integrates production and transportation planning to estimate optimal biomass co-firing ratio in coal power plant. While their mathematical models integrate plant operations with transportation-related decisions and thus assist on co-firing decisions, they exclude various logistics options for biomass procurement, such as multimodal transportation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Feedstock Supply Network: Origin and Destination. Though various types of biomass can fuel co-firing power plants, forest and mill residue were used for this research, as they produce low sulfur and chemical levels (16) and are widely available in the study region. Furthermore, a potential recovery in the U.S. housing and lumber markets could increase the availability of sawmill residues (23).…”
Section: Data Collection and Pre-processingmentioning
confidence: 99%